(untitled) (Journal of Statistical Research, 2025)
In this paper, we introduce a new class of generalized Akash distribution with suitable R code known as weighted generalized Akash distribution has been established. The developed new distribution has been generated by using the weighted technique to its baseline distribution and has been described with its specific statistical features and characteristics. Furthermore, its parameters have been estimated based upon the technique of maximum likelihood estimation. Finally, a real life data set has been investigated and fitted to demonstrate the applicability and flexibility of a new distribution. Journal of Statistical Research 2024, Vol. 58, No. 2, pp. 299-316